This I Believe - Schoonover, Lawrence L. (Tufts Archival Research Center, 2006)
Lawrence Schoonover describes his experiment with ethics in his youth and his questioning of the relevance of the Ten Commandments. He then recounts the awareness of his mistake and how he lives by them and raises his children according to them.